Band structure of Fe based superconductors / Teh Yee Lin - Teh, Yee Lin (2010)
Several iron containing superconductors are discovered in 2008. The discovery introduced a new class of high-temperature superconductors, which are iron-based. The iron-based superconductors do not resemble conventional superconductors and have properties on their own which differ from the cuprates. We have studied the iron selenium, FeSe compound by removing some Se atoms from the lattice forming Fe:Se = 2:1 and 8:6 and also by replacing the Se vacancy with tellurium, samarium and oxygen atoms forming Fe:Se:Te = 2:1:1 and 8:6:2, Fe:Se:O = 8:6:2 and 8:4:2, FeSeSmO, FeSeTeO, Fe2SeSm2O2, FeSeTeSmO and FeTeSmO. The band structures for each lattice are calculated by using the density-functional theory (DFT) in the local density approximation (LDA). The calculation is done by using polarized as well as unpolarised orbitals. The density of states (DOS) of each compound is also calculated. It is found that the gap is highly anisotropic. There is a pronounced effect on the energy gap upon removing some Se atoms from the lattice as well as substitution of other atoms into the FeSe lattice. The energy gap is reduced by a large amount of energy compared to the pure FeSe lattice. It was also found that the normal state gap also reduces upon oxidation. The normal state energy gap reduction produced by doping is related to the increase in the transition temperature of the superconductor.